An Input for Stakeholders’ Management and Engagement Primer (SMEP) of Basic Education in the New Normal in Laguna Cluster, Philippines Insight - Melanie C. Caňo; Consorcia S. Tan, EdD; Marcial M. Bandoy, EdD; Albert D. Yazon, EdD; Lerma P. Buenvinida, EdD (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Crafting contingency plans and interventions in the Philippines' basic education in the new normal is the main concern of the study. Thus, stakeholders’ support for basic education and the school’s implementation in Laguna cluster for the school year 2020-2021 are also determined in this study. Descriptive correlational design was utilized in which 650 individuals served as respondents who are a combination of school heads, master teachers, and teachers in the city schools’ division in Laguna. The result of the study revealed that there is a significant and positive correlation between stakeholder support and the degree of basic education delivery in the new normal, according to Pearson's Coefficient of Correlation. Stakeholder support for the implementation of basic education in the new normal was moderated by school size and demonstrated a high substantial relationship in terms of Learning Environment, Learning Support, Technology Support, Training and Development, and Direct Assistance. The use of regression coefficient showed that there is an immersive impact of school size on programs and tools in the delivery of basic education in the modern normal. On the other hand, there is no discernible interactive impact on the school scale. Hence, the empirical findings of the study were the basis of the researcher for the creation of a comprehensive contingency intervention plan. The Stakeholders’ Management and Engagement Primer (SMEP) was crafted and recommended to all school leaders to bridge the gap between the stakeholders’ support and the schools participating in the new normal adoption of basic education in Laguna cluster, Philippines.